Program Pemberdayaan Sebagai Aktivitas Corporate Social Responsibility Studi Kasus Pemberdayaan Penderes di Pangandaran - Rahmad Efendi (Umbara, 2016)
Abstract This article examines the phenomenon of the implementation of community empowerment program as the Corporate Social Responsibility (CSR) activity, which is used as a strategy to control the supply chain of raw materials. This paper prepared using qualitative research methods with field study at Pangandaran District, West Java. The Pangandaran Tappers Community Empowerment Program has been run by PT Ultrava since 2012 until 2014. The program is aimed to manage the brown sugar supply chain problems in Pangandaran that caused by the tappers. For that purpose, Ultrava running the govermentality agenda against all of the brown sugar supply chain actors in Pangandaran. The govermentality agenda use the biopolitic and subjectivity process, to change the tappers became the obedient subject to the will of Ultrava. Keywords : CSR, Empowerment, Govermentality Abstrak Artikel ini mengkaji fenomena pelaksanaan program pemberdayaan masyarakat sebagai Corporate Social Responsibility (CSR), yang digunakan sebagai strategi untuk mengendalikan rantai pasokan bahan baku. Artikel ini disusun dengan menggunakan metode penelitian kualitatif dengan studi lapangan di Kabupaten Pangandaran, Jawa Barat. Program Pemberdayaan Penderes Pangandaran telah dijalankan oleh PT Ultrava sejak 2012 hingga 2014. Program ini bertujuan untuk mengelola masalah rantai pasokan gula di Pangandaran yang disebabkan oleh penderes. Untuk itu, Ultrava menjalankan agenda govermentality terhadap semua pelaku rantai pasokan gula di Pangandaran. Agenda govermentality tersebut menggunakan proses biopolitic dan subjectivity, untuk mengubah penderes menjadi subyek yang patuh kepada kehendak Ultrava. Kata Kunci – CSR, Pemberdayaan, Kepengaturan